Revolution Unfolding: The Historical Present between ‘Real Time’ and Latency in Found Footage Filmmaking (Cinéma & Cie. Film and Media Studies Journal, 2024)
The inextricable connection between uprisings and technologies of audiovisual recording and broadcasting, especially within an ecology of digital networks, suggests the possibility to follow events in ‘real time’. This paper asks how filmmakers explore the complexities of this notion—and the questions of spectatorship, temporality and mediation that are attached to it—by drawing on the an-archive of protest footage. It is especially interested in the ways in which found footage filmmaking manages to (re-)create a sense of the historical present without resorting to a flat presentism. How do filmmakers re- and deconstruct experiences of ‘real time’ and the fraught notion of immediacy it proposes? How do their narrations attempt to give shape to the openness of the present moment? And how do they negotiate the latent historicity of events? To approach these questions, the paper undertakes a close reading of two films, Fragments of a Revolution (anonymous, 2011) and Videograms of a Revolution (Harun Farocki and Andrei Ujică, 1992), thus drawing a connection between digital and analogue ‘guerilla images’.
Keywords: Latency; Real time; Historical experience; Genre; Spectatorship